A Tribo Melastomeae (Melastomataceae) no estado de Goiás, Brasil - Oliveira, Ana Luiza Freitas (2014)
The Melastomataceae has about 150 genera and 4.500 species, with a pantropical distribution, with the highest concentration of species in the New World. Brazil it is the sixth largest family of angiosperms, with 67 genera and about 1324 species, occurring in very diverse environments. Melastomeae is considered one of the most important tribes for Brazil with about 280 species and 22 genera. The present study aimed a) to provide a list of species of Melastomeae tribe found in Goiás b) the systematic treatment with identification key of genera and species, morphological description, taxonomic remarks, geographical data and illustrations of the main diagnostic characters of the species c) the validation of two new species of Tibouchina. About 2000 specimens of Melastomeae deposited in the herbaria CEN, ESA, FLOR, HUEFS, HUEG, HUFG, HUFU, IBGE, MBM, R, RB, SP, SPF, UB and UEC were analyzed. In order to complement the collections for the state of Goiás, fieldwork was carried out in Cristalina, Serra Dourada, Serra dos Pireneus and Quirinópolis in 2012 and 2013. All collected material is deposited in the herbarium HUFU, of Federal University of Uberlândia. Melastomeae is represented by 40 species in Goiás. Tibouchina Aubl., with 21 species, is the most representative genus, Pterolepis (DC.) Miq. and Siphanthera Pohl. ex DC. present five species each, Acisanthera P. Browne. four, while Comolia DC., Desmoscelis Naud., Macairea DC., Marcetia DC. and Poteranthera Bong. are represented by one species each. During these studies, two new species of Tibouchina were found and compared with herbarium specimens previously determined as T. albescens and T. nigricans. Although recognized by Alfred Celestin Cogniaux in the late nineteenth century, these taxa were never validly published and thus we propose the validation of these names.